1998
DOI: 10.1007/s004200050275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methyl ethyl ketone, acetone, or toluene coadministration on 2,5-hexanedione concentration in the sciatic nerve, serum, and urine of rats

Abstract: Coadministration of 2,5-HD with MEK, AC, or TO can increase the concentration and AUC of 2,5-HD in serum and the sciatic nerve, and these increases can be further enhanced by an increase in the concomitant doses of MEK and AC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Yasui et al (1995) showed that MEK is capable of prolonging the 2,5-HD T 1/2 in the blood, which was thought to relate to the potentiation of 2,5-HD neurotoxicity by MEK. Zhao et al (1998) showed that MEK (as well as acetone and toluene) decreased the elimination rate constants of 2,5-HD in co-administration groups. These empirical observations consistently suggest a qualitative relationship between 2,5-HD T 1/2 and 2,5-HD and MEK concentrations.…”
Section: Parametermentioning
confidence: 97%
“…Yasui et al (1995) showed that MEK is capable of prolonging the 2,5-HD T 1/2 in the blood, which was thought to relate to the potentiation of 2,5-HD neurotoxicity by MEK. Zhao et al (1998) showed that MEK (as well as acetone and toluene) decreased the elimination rate constants of 2,5-HD in co-administration groups. These empirical observations consistently suggest a qualitative relationship between 2,5-HD T 1/2 and 2,5-HD and MEK concentrations.…”
Section: Parametermentioning
confidence: 97%